Equivalence between the application of entransy and entropy generation - Oliveira, Santiago del Rio [UNESP]; Milanez, Luiz Fernando (Elsevier B.V., 2014)
Recently, a group of researchers proposed the concept of entransy by analogy with the electrical energy stored in a capacitor, the entransy being a measure of the ability of a body or a system to transfer heat. In comparative terms, the entransy dissipation rate is related with the loss of heat transfer ability just like the exergy destruction rate is proportional to the loss of work ability, being these losses caused by the irreversibilities related to the thermodynamic processes. Some authors have questioned the need for the concept of entransy, claiming that this concept is only an extension of a well established theory of heat transfer. The objective of this work is show the equivalence between the application of the concepts of entransy and entropy generation rate, which can be verified using various application examples. The application examples used here are the thermodynamic modeling of three physical models of solar energy collectors and a physical model of a sensible heat storage system. Analytical results are shown and compared. The results showed that the application of the concept of entransy provided identical expressions obtained by the concept of entropy generation, indicating a duplication of concepts. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Entransy; Entropy; Exergy; Solar collectors; Sensible energy storage